Electrochemical Detection of H2O2 Using Bi2O3/Bi2O2Se Nanocomposites - Pooja D. Walimbe; Rajeev Kumar; Amit Kumar Shringi; Obed Keelson; Hazel Achieng Ouma; Fei Yan (Nanomaterials)
The development of high-performance hydrogen peroxide (H2O2) sensors is critical for various applications, including environmental monitoring, industrial processes, and biomedical diagnostics. This study explores the development of efficient and selective H2O2 sensors based on bismuth oxide/bismuth oxyselenide (Bi2O3/Bi2O2Se) nanocomposites. The Bi2O3/Bi2O2Se nanocomposites were synthesized using a simple solution-processing method at room temperature, resulting in a unique heterostructure with remarkable electrochemical characteristics for H2O2 detection. Characterization techniques, including powder X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), and scanning electron microscopy (SEM), confirmed the successful formation of the nanocomposites and their structural integrity. The synthesis time was varied to obtain the composites with different Se contents. The end goal was to obtain phase pure Bi2O2Se. Electrochemical measurements revealed that the Bi2O3/Bi2O2Se composite formed under optimal synthesis conditions displayed high sensitivity (75.7 µA µM−1 cm−2) and excellent selectivity towards H2O2 detection, along with a wide linear detection range (0–15 µM). The superior performance is attributed to the synergistic effect between Bi2O3 and Bi2O2Se, enhancing electron transfer and creating more active sites for H2O2 oxidation. These findings suggest that Bi2O3/Bi2O2Se nanocomposites hold great potential as advanced H2O2 sensors for practical applications.